Anatomical characters used to delimit species of some genera of Brassicaceae in Iraq. - Al-Saadi, Sahar A. A. Malik; Qader, Karzan Omer; Fetah, Heyder Uthman (Sulaimani Journal for Pure and Applied Sciences, 2019)
The anatomical characters of the leaf epidermal cells and trichomes of 13 species of Brassicaceae family were studied by light and scanning electron microscopy. The results showed cell walls thicker in Cheiranthus cheiri, Camelina rumelica, Biscutella didyma; and also, in lower epidermis of Crambe orientalis. While they were thin in Calepina irregularis, Lobularia maritima, Nasturtium officinale and Thlaspi perfoliatum. Cells of upper epidermis were with strongly undulate anticlinal cell walls in Capsella bursa-pastoris, Draba bruniifolia, Nasturtium officinale and Sameraria stylophora. Cells were with sinuous anticlinal walls in Calepina irregularis, Cheiranthus cheiri and Biscutella didyma. There were straight-sinuate anticlinal cell walls in the rest of the species studied. Five types of stomatal complex were found: 1. Anisocytic (Cruciferous), 2. Anomocytic (Rununculaceous), 3. Hemiparacytic, 4. Paracytic, in Cheiranthus cheiri, Crambe orientalis, Nasturtium officinale, Cardaria drapa subsp. draba and Thlaspi perfoliatum, and 5. Tetracytic in Cardaria draba and Thlaspi perfoliatum. The highest Stomatal index percent was 36.4% on the abaxial surface of Cheiranthus cheiri, and the lowest 7.81% in abaxial of Draba bruniifolia. Eight trichome types are distinguished: Simple, T-shaped, Y-shaped, V-shaped, Vesiculate, Clavate, Dendroid, Stellate and Long membranous. In addition, glabrous species also were found.
Keywords: Epidermis; Brassicaceae; Trichomes; Stomata